The Role of Collagen XVII in Cancer: Squamous Cell Carcinoma and Beyond - Jones, Virginia A.; Patel, Payal M.; Gibson, Frederick T.; Cordova, Adriana; Amber, Kyle T. (Frontiers in Oncology, 2020)
Alterations in the extracellular matrix (ECM) likely facilitate the first steps of cancer cell metastasis and supports tumor progression. Recent data has demonstrated that alterations in collagen XVII (BP180), a transmembrane protein and structural component of the ECM, can have profound effects on cancer invasiveness. Collagen XVII is a homotrimer of three α1 (XVII) chains. Its intracellular domain contains binding sites for plectin, integrin β4, and BP230, while the extracellular domain facilitates interactions between the cell and the ECM. Collagen XVII and its shed ectodomain have been implicated in cell motility and adhesion and are believed to promote tumor development and invasion. A strong association of collagen XVII ectodomain shedding and tumor invasiveness occurs in squamous cell carcinoma (SCC). Aberrant expression of collagen XVII has been reported in many epithelial cancers, ranging from squamous cell carcinoma to colon, pancreatic, mammary, and ovarian carcinoma. Thus, in this review, we focus on collagen XVII's role in neoplasia and tumorigenesis. Lastly, we discuss the importance of targeting collagen XVII and its ectodomain shedding as a novel strategy to curb tumor growth and reduce metastatic potential.